2017
DOI: 10.18388/abp.2016_1334
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in Cardiovascular Diseases

Abstract: Cardiovascular Diseases (CD) are currently one of the most common causes of death. Because heart related deaths occur on such an enormous scale this phenomenon is referred to as an epidemic. Chronic and acute injury of the heart could be an effect of cardiac remodeling, which is a result of molecular, cellular and interstitial changes, influenced by hemodynamic load or neurohormonal activation (Cohn et al., 2000). These small deviations in cardiac activity and morphology may lead to an enormous negative effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This regulation is also present in the self-renewal of stem cells and the differentiation of a variety of cell lineages (7). It is confirmed that the generation of miRNAs can interfere with the process of angiogenesis and the function of vascular endothelial cells (8).…”
Section: Introductionmentioning
confidence: 78%
“…This regulation is also present in the self-renewal of stem cells and the differentiation of a variety of cell lineages (7). It is confirmed that the generation of miRNAs can interfere with the process of angiogenesis and the function of vascular endothelial cells (8).…”
Section: Introductionmentioning
confidence: 78%
“…Specifically, the Human Cardiovascular Disease miRNA array (Qiagen, Germany) was examined in 20 individuals from the HERITAGE Family Study. This array includes 84 miRNAs that are differentially regulated during CVD progression and have been associated with CVD in multiple studies involving a variety of CVD models and a variety of miRNA profiling methodologies 2028 . We hypothesized that regular exercise would significantly alter the circulating miRNAs related to CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, researchers have been focusing on the role of microRNAs in cellular, molecular, and various disorders and diseases (17,18).…”
Section: Discussionmentioning
confidence: 99%